Mirror therapy for postoperative functional recovery after surgical repair of upper-limb traumatic peripheral nerve injuries: a systematic review and meta-analysis - Xu, Jincheng; Lin, Dandan; Jian, Lina; Liao, Wei; Yang, Shuming (Frontiers in Neurology, 2025)
BackgroundTraumatic peripheral nerve injuries of the upper limb often lead to substantial motor and sensory deficits, posing significant challenges to functional recovery and quality of life. Mirror therapy, a visually guided neurorehabilitation technique, has shown potential in enhancing upper limb function, yet its effectiveness in traumatic peripheral nerve injuries remains inconclusive.MethodsThis systematic review and meta-analysis followed PRISMA 2020 guidelines. Randomized controlled trials involving adult patients with upper limb traumatic peripheral nerve injuries treated with mirror therapy were identified through searches of seven major databases up to Augst 2025. Methodological quality was assessed using the PEDro scale, and pooled analyses were performed using standard mean differences with 95% confidence intervals.ResultsSeven clinical studies involving 112 participants were included and five randomized controlled trials contributed to the meta-analysis. Mirror therapy significantly improved hand function measured by the Rosen Score (SMD = 0.24; 95% CI: 0.02 to 0.46; p = 0.03; I2 = 0%). Improvements in grip strength (SMD = 0.45; p = 0.26) and sensory outcomes (SWM: SMD = 1.05; p = 0.07; 2PD: SMD = 0.45; p = 0.26) did not reach statistical significance. Pain-related outcomes were inconsistently reported. Subgroup analysis was not feasible due to intervention heterogeneity and limited sample sizes. Certainty of evidence was moderate for hand function and low to very low for other outcomes.ConclusionMirror therapy may offer modest benefits in hand function recovery following upper limb traumatic peripheral nerve injury. However, current evidence is limited by small sample sizes, methodological heterogeneity, and low study quality. No significant effects were observed for sensory or pain-related outcomes. Further high-quality randomized controlled trials with standardized protocols and long-term follow-up are needed to establish the clinical efficacy and optimize the use of mirror therapy in this population.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023437659.